A new genus and species of cardinalfish (Percomorpha, Apogonidae, Sphaeramiini) from the coastal waters of Vietnam: luminescent or not? - Fraser, Thomas H.; Prokofiev, Artem M. (Zootaxa, 2016)
Xeniamia atrithorax is a diminutive new genus and new species. The following combination of melanophore patterns is unique among known apogonids: a large cluster of melanophores in the skin anterior to the insertion of the pelvic-fin base, then extending forward along the sides of the isthmus; posterior portion of the oral chamber is black with melanophores extending below the gill apparatus forward along the base of the oral chamber thence along the basibranchials ending posterior to and below the level of the tongue; a line of large melanophores extends along the inner side of the ceratohyals; black to blackish stomach; and the anterior portion of the intestine is mostly pale with few black spots becoming more densely spotted with melanophores past the first bend and black from the second intestinal turn to the anus. The peritoneum is silvery with scattered melanophores that are more densely distributed along the lower portion of the abdominal cavity. There are two pale, large pyloric caeca at the connection between the stomach and intestine. The combination of eight first-dorsal spines, two supernumerary dorsal spines, one supraneural, lacking an ossified basisphenoid, two epurals and fused hypurals 1+2, preopercle with a smooth ridge and edges, fourth dorsal spine longer than third distinguish this cardinalfish from all other genera. This new genus may be related to Jaydia in the Sphaeramiini rather than with the Ostorhinchini or Siphamiini. Possible luminescent activity is inferred from anatomy and unique melanization patterns versus suppression of light from luminescent prey in the alimentary canal. A table lists suspected and known luminescent apogonids.